Renal tubular dysgenesis-a case presentation - Atasay, Begüm; Günlemez, Ayla; Arsan, Saadet; Bakkaloğlu, Sevcan; Tulunay, Özden; Yalçınkaya, Fatoş (The Turkish Journal of Pediatrics, 2004)
Renal tubular dysgenesis (RTD) is a lethal, developmental anomaly of the fetal kidney characterized by a defect in differentiation of the proximal and distal convoluted tubules. It is usually associated with oligohydramnios in later pregnancy and Potter's syndrome. A neonate with typical features who presented with mild respiratory distress, dysmorphic appearance and anuria is described. At the age of seven days, peritoneal dialysis was started and was continued until the death of the baby at the age of three months. The diagnosis was made on the bases of clinical and ultrasonographic findings confirmed by renal biopsy. A review of the literature showed that this is the first case of RTD reported in Turkey.